Socioeconomic and Clinical Profile of Diabetic Foot Ulcer Patients with National Health Insurance during Pandemic COVID-19 in Indonesia - Fitrianingsih Fitrianingsih; Rani Sauriasari; Em Yunir; Agusdini Banun Saptaningsih (Jurnal Kefarmasian Indonesia, 2025)
During the COVID-19 pandemic, the mandatory lockdown and government policy in prioritizing COVID-19 patients affected patients with diabetic foot ulcers (DFU). Most DFU patients experienced difficulties visiting hospitals and covering the cost of treatment, which led to changes in patient characteristics, poor clinical outcomes, and higher total costs. This study aimed to determine the sociodemographic and clinical outcomes profile of DFU patients under National Health Insurance (NHI-DFU) during the COVID-19 pandemic and their effect on the total direct medical cost. This cross-sectional study enrolled all JKN-DFU hospitalized patients at the National Referral Hospital, Cipto Mangunkusumo Hospital (RSCM), Jakarta, Indonesia, during COVID-19 pandemic (March 2nd, 2020, to December 2022). We used electronic health records, electronic billing, and foot registry systems. Participants were over 18 years old in a single admission period. Statistical analysis used Mann-Whitney and Kruskal-Wallis; Post hoc used the Mann-Whitney test. There were 158 JKN-DFU patients with predominated criteria: female patients (55.1%), aged over 60 years old (55.1%) with a mean age of 59.3 ± 11.0 years, unemployed (63.9%), intermediate educated (41.8%), Jakarta residents (68.4%), and mostly severe infection (63.3%). The total cost was much higher than INA-CBG’s coverage. The occupation (p=0.048), length of stay (LOS) (p=0.001), and amputation status (p<0.001) significantly affected total cost. Civil servants, longer LOS, and major amputation status leading higher total costs.